A multi-faceted role of dual-state dopamine signaling in working memory, attentional control, and intelligence - Matzel, Louis D.; Sauce, Bruno (Frontiers in Behavioral Neuroscience, 2023)
The balance of dopamine D1 (D1R) and D2 (D2R) receptors can influence intrinsic currents and synaptic transmission in frontal cortical regions. Here, we review evidence from human, animal, and computational studies that suggest that this balance (in density, activity state, and/or availability) is critical for executive functions such as attention and working memory. In this system, D1 receptors dominate responding during stable periods of short-term memory maintenance (requiring attentional focus), while D2 receptors play a more specific role during periods of instability such as changing environmental or memory states (requiring attentional disengagement). We then bridge these ideas with some known properties of human intelligence. Starting from theories that place executive functions at the center of the sphere of intelligence (such as hierarchical models and the process overlap theory), we propose that dual-state dopamine signaling might be a causal contributor to individual differences in intelligence. Although this is a tentative hypothesis, it is consistent with an array of available evidence and has a high degree of explanatory value, and we suggest future directions and empirical tests using genetic data.